Mixed species biofilms of Fusobacterium necrophorum and Porphyromonas levii impair the oxidative response of bovine neutrophils in vitro. (October 2017) - Lockhart, Joey S.; Buret, Andre G.; Ceri, Howard; Storey, Douglas G.; Anderson, Stefanie J.; Morck, Douglas W.
Abstract: Biofilms composed of anaerobic bacteria can result in persistent infections and chronic inflammation. Host immune cells have difficulties clearing biofilm-related infections and this can result in tissue damage. Neutrophils are a vital component of the innate immune system and help clear biofilms. The comparative neutrophilic response to biofilms versus planktonic bacteria remains incompletely understood, particularly in the context of mixed infections. The objective of this study was to generate mixed species anaerobic bacterial biofilms composed of two opportunistic pathogens, Fusobacterium necrophorum and Porphyromonas levii, and evaluate neutrophil responses to extracellular fractions from both biofilms and planktonic cell co-cultures of the same bacteria. Purified bovine neutrophils exposed to culture supernatants from mixed species planktonic bacteria showed elevated oxidative activity compared to neutrophils exposed to biofilms composed of the same bacteria. Bacterial lipopolysaccharide plays a significant role in the stimulation of neutrophils; biofilms produced substantially more lipopolysaccharide than planktonic bacteria under these experimental conditions. Removal of lipopolysaccharide significantly reduced neutrophil oxidative response to culture supernatants of planktonic bacteria. Oxidative responses to LPS-removed biofilm supernatants and LPS-removed planktonic cell supernatants were similar. The limited neutrophil response to biofilm bacteria observed in this study supports the reduced ability of the innate immune system to eradicate biofilm-associated infections. Lipopolysaccharide is likely important in neutrophil response; however, the presence of other extracellular, immune modifying molecules in the bacterial media also appears to be important in altering neutrophil function. Highlights: Anaerobic mixed-species biofilms were generated in a novel porous membrane system. Planktonic bacteria produced significantly less LPS than biofilm bacteria. Planktonic bacteria stimulated neutrophils more extensively than biofilm bacteria.